Business analytics: Methods, models, and decisions - Evan, James R. (Uttar Pradesh, India Pearson, 2020)
James R. Evans Professor, University of Cincinnati College of Business James R. Evans is professor in the Department of Operations, Business Analytics, and Information Systems in the College of Business at the University of Cincinnati. He holds BSIE and MSIE degrees from Purdue and a PhD in Industrial and Systems Engineering from Georgia Tech. Dr. Evans has published numerous textbooks in a variety of business disciplines, including statistics, decision models.